A Double-blind, Randomized, Placebo-controlled Study of the Efficacy and Safety of Duloxetine for the Treatment of Chronic Pain Due to Osteoarthritis of the Knee - Chappell, Amy S.; Desaiah, Durisala; Liu-Seifert, Hong; Zhang, Shuyu; Skljarevski, Vladimir; Belenkov, Yuri; Brown, Jacques P. (Pain practice, 2011)
Objective:  To evaluate the efficacy and safety of duloxetine in the treatment of chronic pain due to osteoarthritis of the knee. Methods:  This was a 13‐week, randomized, double‐blind, placebo‐controlled trial in patients meeting American College of Rheumatology clinical and radiographic criteria for osteoarthritis of the knee. At baseline, patients were required to have a ≥ 4 weekly mean of the 24‐hour average pain ratings. Patients were randomized to either duloxetine 60 mg once daily (QD) or placebo. At week 7, the duloxetine dosage was increased, in a blinded fashion, to 120‐mg QD in patients reporting < 30% pain reduction. The primary efficacy measure was Brief Pain Inventory (BPI) 24‐hour average pain. Secondary efficacy measures included Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC); Clinical Global Impressions of Severity (CGI‐S). Safety and tolerability was also assessed. Results:  Of the total (n = 256) patients, 111 (86.7%) in placebo group and 93 (72.7%) in duloxetine group completed the study. Patients treated with duloxetine had significantly (P ≤ 0.001) greater improvement at all time points on BPI average pain and had significantly greater improvement on BPI pain severity ratings (P ≤ 0.05), WOMAC total (P = 0.044) and physical functioning scores (P = 0.016), and CGI‐S (P = 0.009) at the study endpoint. Frequency of treatment‐emergent nausea, constipation, and hyperhidrosis were significantly higher in the duloxetine group (P ≤ 0.05). Significantly more duloxetine‐treated patients discontinued the trial because of adverse events (P = 0.002). Conclusions:  Treatment with duloxetine 60 mg to 120 mg QD was associated with significant pain reduction and improved function in patients with pain due to osteoarthritis of the knee.